Impairment of Cerebrovascular Reactivity by Methionine-Induced Hyperhomocysteinemia and Amelioration by Quinapril Treatment - Chao, Chia-Lun; Lee, Yuan-Teh (Stroke (1970), 2000)
Background and Purpose —Human studies have shown that methionine-induced hyperhomocysteinemia impairs brachial artery endothelial function via decreasing nitric oxide activity. However, the effect of homocysteine on cerebrovascular reactivity (CVR), which has been reported to be nitric oxide related in experimental and animal studies, remains unclear in humans. Inhibition of angiotensin-converting enzyme may improve nitric oxide–mediated cerebral as well as peripheral endothelial function. The aim of the present study was to investigate the effect of methionine-induced hyperhomocysteinemia on CVR before and after treatment with quinapril, an angiotensin-converting enzyme inhibitor, in healthy adults. Methods —Plasma homocysteine and CVR were measured at baseline and 4 hours after methionine load (0.1 g/kg body wt) before and after quinapril treatment (10 mg/d for 1 week) in both younger and older groups. CVR was assessed by transcranial Doppler ultrasonography, measuring the percent increase of flow velocity in the middle cerebral artery after brief carotid compression (expressed as transient hyperemic response ratio [THRR]). Results —Homocysteine levels were significantly increased after methionine load either before or after quinapril treatment in both groups. Before quinapril treatment, postmethionine THRR was preserved in younger adults (24.2±5.3% versus 23.8±6.3% at baseline, P =0.73) and decreased in older adults (12.9±2.2% versus 21.8±4.0% at baseline, P <0.001). After quinapril treatment, postmethionine THRR was preserved in both groups (24.5±5.9% versus 24.0±5.0% at baseline, P =0.42 in younger adults; 20.4±3.9% versus 21.3±3.3% at baseline, P =0.35 in older adults). Conclusions —Our study suggests that methionine-induced hyperhomocysteinemia may be causally associated with impairment of CVR in older normal subjects.